Ice cold heart - Tracy, P. J (Tracy, P. J. Monkeewrench novel., 2019)
It's a bitter winter in Minnesota--too cold to kill. There hasn't been a murder for a month, but the lull quickly comes to an end for Detectives Leo Magozzi and Gino Rolseth, when they're called to the gruesome homicide of Kelly Ramage. Found in a friend's vacant house, this was no random attack, and clues reveal that she was living a very dangerous secret life. Magozzi and Gino trace her steps back to an art gallery where she was last seen alive. The gallery seems like a dead end, but the art is disturbing and exploitative. It may very well be inspiring a sadistic killer, because in this instance, art doesn't imitate life, it imitates death. Tipped off about a year-old murder that is a mirror-image of Kelly's crime scene, Gino and Magozzi enlist the aid of Grace MacBride and her eccentric, tech genius partners in Monkeewrench Software to help them decipher the digital trail that might connect the cases. As coincidences emerge, Magozzi, Gino, and the team have to work around the clock at breakneck pace to unravel a series of clues that form the framework of a larger, more sweeping, and insidious conspiracy than any of them could have imagined. Is Kelly the last person to die or just the most recent? And is there any way to stop it?